Tumor Necrosis Factor-α Gene Expression in Epicardial Adipose Tissue is Related to Coronary Atherosclerosis Assessed by Computed Tomography - Kitagawa, Toshiro (J Atheroscler Thromb, 2018)
Aims: Tumor necrosis factor (TNF)-α reportedly has key pro-inflammatory properties in both atherosclerosis and adipocytes. To further investigate the biologic impact of epicardial adipose tissue (EAT) on coronary atherosclerosis, we evaluated the relationship between TNF-α gene expression in EAT and clinically-assessed coronary atherosclerosis on computed tomography (CT). Methods: We studied 47 patients before cardiac surgery (coronary artery bypass grafting [CABG], n = 26; non-CABG, n = 21), assessing visceral adipose tissue (VAT) area, EAT volume, coronary calcium score (CCS), and the presence of non- and/or partially-calcified coronary plaque (NCP) on CT angiography. EAT and subcutaneous adipose tissue (SAT) samples were obtained during cardiac surgery. TNF-α mRNA in EAT was measured using quantitative real-time PCR, and normalized to that of SAT as control adipose tissue. Results: There was no difference in the TNF-α expression level between patients scheduled for CABG and non-CABG surgery (p = 0.23), or among the subgroups based on CCS (p = 0.68), while patients with NCP had the higher TNF-α expression level than those without NCP (median [interquartile range], 2.50 [1.01–5.53] versus. 1.03 [0.64–2.16], p = 0.022). On multivariate analysis adjusted for age, sex, coronary risk factors, statin therapy, CABG versus non-CABG, VAT area, and EAT volume, the presence of NCP had close correlation with the elevated TNF-α expression level (β= 0.79, p = 0.003). Conclusions: TNF-α expressed regionally in EAT may exert potent effects on the progression of coronary atherosclerosis, suggesting a contribution of EAT to coronary artery disease through behavior of molecule.